Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

ISRO | ISRO CS 2008 | Question 23

  • Last Updated : 20 Nov, 2018

The Boolean expression ( A + C’)(B’+ C’) simplifies to
(A) C’ + AB’
(B) C’ (A’ + B)
(C) B’C’ + AB’
(D) None of these.


Answer: (A)

Explanation: The following expression can be simplified as:

(A + C')(B'+ C')
= AB' + AC' + B'C' + C'
= AB' + C'(A + B' + 1)  // 1 + A = 1
= AB' + C'

Option (A) is correct.

Quiz of this Question

My Personal Notes arrow_drop_up
Recommended Articles
Page :